Nitric oxide production by polymorphonuclear leucocytes in infected cystic fibrosis sputum consumes oxygen. (July 2014) - Kolpen, M.; Bjarnsholt, T.; Moser, C.; Hansen, C. R.; Rickelt, L. F.; Kühl, M.; Hempel, C.; Pressler, T.; Høiby, N.; Jensen, P. Ø.
Summary Chronic Pseudomonas aeruginosa lung infection in cystic fibrosis (CF) patients is characterized by persisting mucoid biofilms in hypoxic endobronchial mucus. These biofilms are surrounded by numerous polymorphonuclear leucocytes (PMNs), which consume a major part of present molecular oxygen (O2) due to production of superoxide (O2−). In this study, we show that the PMNs also consume O2 for production of nitric oxide (NO) by the nitric oxide synthases (NOS) in the infected endobronchial mucus. Fresh expectorated sputum samples (n = 28) from chronically infected CF patients (n = 22) were analysed by quantifying and visualizing the NO production. NO production was detected by optode measurements combined with fluorescence microscopy, flow cytometry and spectrophotometry. Inhibition of nitric oxide synthases (NOS) with NG‐monomethyl‐L‐arginine (L‐NMMA) resulted in reduced O2 consumption (P < 0·0008, n = 8) and a lower fraction of cells with fluorescence from the NO‐indicator 4‐amino‐5‐methylamino‐2′, 7′‐difluorofluorescein diacetate (DAF‐FM) (P < 0·002, n = 8). PMNs stained with DAF‐FM and the superoxide indicator hydroethidine (HE) and host cells with inducible NOS (iNOS) were identified in the sputum. In addition, the production of the stable end‐products of NO in CF sputum was correlated with the concentration of PMNs; NO3− (P < 0·04, r = 0·66, n = 10) and NO2− (P< 0·006, r = 0·78, n = 11). The present study suggests that besides consumption of O2 for production of reactive oxygen species, the PMNs in CF sputum also consume O2 for production of NO.